Antiviral drugs and vaccines - Borah P.; Hazarika S.; Morsy M.A.; Goyal M.; Chettri A.; Venugopala K.N.; Mohanlall V.; Acharya P.C.; Deb P.K.; Mailavaram R.P. (My University, 2025)
Humankind is adopting different countermeasures to control viral infections, including the development of antiviral agents for treatments and vaccines as a prophylactic measure to prevent the casualties of viral diseases. Since the 1950s, the antiviral drug discovery was challenged by the emergence of various viral infections such as acquired immune deficiency syndrome, hepatitis B virus (HBV)/hepatitis C virus (HCV), and the coronavirus infections such as severe acute respiratory syndrome, Middle East respiratory syndrome, and COVID-19. Most of the current antiviral drugs interfere with the critical stages of the virus attachment to the host cells or the viral replication cycle. More than 100 antiviral drugs or their combinations have been approved in the past decades for the treatment of nine human viral infections, viz. herpes simplex virus, varicella–zoster virus, human cytomegalovirus, HBV, HCV, influenza virus, respiratory syncytial virus, variola virus, and human immunodeficiency virus infections. Given the variability of antivirals, this chapter describes the antivirals approved for the aforementioned nine viral diseases along with a brief overview of SARS-CoV-2 infection and its treatment strategies. Here, we also discuss the viral vaccines, approaches to overcome viral adaptations, and the newer agents undergoing clinical development. © 2023 Elsevier Inc. All rights reserved.